The Ability of Cocoa Clonal Seeds for Alternative Rootstock in Seedlings Production - Juwahir, Nurella Eziwana; M Khatta, Aida Nabihah; Awang Besar@Raffie, Normah; Jalloh, Mohamadu Boyie; Tabet, Tamer A.; Muda, Boney; Hassan, Affendy (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Currently, there is a shortage of cocoa clonal seedlings utilizing rootstock from the cocoa seed clone UIT1 × NA33 in the cocoa industry. Alternative clonal seedlings having comparable or superior growth and root characteristics are needed. This study aimed to evaluate and screen the growth and root performance of selected commercial cocoa seed clones as alternatives to UIT1 × NA33. The experiment used 45 rhizotrons (15 selected clones including UIT1 × NA33 as a control, with three replicates each) to grow roots to a one-meter depth under a completely randomized design (CRD). Height increment, root intensity (RI), and root depth (RD) were measured throughout the study. Sixteen weeks after transplanting (WAT), all tubes were harvested for dried shoot biomass (DSB), dried root biomass (DRB), root length density (RLD), and specific root length (SRL) measurement. Results showed no significant difference (P>0.05) among the seed clones based on one-way ANOVA followed by Tukey's HSD test. In conclusion, the clones KKM 1, PBC 123, QH 22, and MCBC 1 exhibited good root performance and growth, indicating their potentials as alternative rootstock for UIT1 × NA33.